Longitudinal study on health-related quality of life and multimorbidity: from trajectories to outcomes in China - Du, Jiancai; Qi, Ai; Wang, Wenlong; Ma, Ximin; He, Jiahui; Hu, Qi; Chen, Kexin; Qiao, Hui (Frontiers in Public Health, 2025)
BackgroundThe association between multimorbidity and health-related quality of life has been extensively studied. This study aimed to investigate the longitudinal association between multimorbidity and health-related quality of life in a rural Chinese population. Specifically, we sought to: (1) examine how the trajectory of multimorbidity burden influences subsequent health-related quality of life, and (2) explore how the trajectory of health-related quality of life, in turn, influences the incidence of multimorbidity.MethodsBased on a longitudinal survey of the health status of rural community residents aged 18 years and above in 2012, 2015, 2019, and 2022, a group-based trajectory model was used to fit the trajectory of multimorbidity and health-related quality of life utility index over time. Multinomial logistic regression was employed to analyze the association trajectory with outcomes between the health-related quality of life utility index and multimorbidity. A series of sensitivity analyses was used to ensure the robustness of results.ResultsA total of 1,398 residents who completed the four follow-up surveys were included in the analysis. Two trajectories of the health-related quality of life utility index were identified, and the risk of two and three or more multimorbidities in the decline trajectory was 1.95 and 3.78 times greater than that in the stable trajectory, respectively. Two trajectories of multimorbidity were identified: the health-related quality of life utility index decreased by 0.09 in the rapid increase trajectory compared with the slow increase trajectory. The results of the sensitivity analysis remained robust.ConclusionThe trajectory of the health-related quality of life utility index can be used to predict the risk of multimorbidity. Heterogeneous trajectories of chronic disease multimorbidity development lead to differential impacts on the health-related quality of life utility index.